Implementasi Kegiatan Ekstrakurikuler Dalam Membentuk Karakter Peserta Didik di MTs. Al-Ma’arif Wuluhan Jember - Amirotun Nahdliyah; Arina Faiqotul Himmah (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2020)
This study is to answer three problem formulations, namely (1) How are extracurricular activities at MTs. Al-Maarif Wuluhan Jember? (2) How is the implementation of extracurricular activities in shaping the character of students in MTs. Al-Maarif Wuluhan Jember? (3) What are the supporting and inhibiting factors for extracurricular activities in MTs. Al-Maarif Wuluhan Jember? Therefore, the type of research chosen is qualitative with a descriptive approach. Data analysis with the process of data reduction, data presentation and conclusions. From the observation process, interviews and documentation resulted in the following conclusions: (1) Extracurricular activities at MTs. Al-Maarif Wuluhan Jember is carried out only on Saturdays as many as 8 types of curricular activities are sustainable, namely the Olympics Studio, Tsalma Scout Scouts, Pagar Nusa, Volly Ball, Tsalma Futsal Club, Badminton, Sholawat Majlis, and Tahfidzul Quran. (2) The implementation of extracurricular activities in shaping the character of students is contained in scout extracurricular activities, namely camps, bonfires and ceremonies. (3) Supporting factors include the presence of competitions, the presence of alumni, active coaches, support from parents and additional time on Friday afternoons. The inhibiting factors are the lack of student commitment, no definite syllabus, lack of facilities and infrastructure, teaching staff and funds.